2016
DOI: 10.3390/su8030216
|View full text |Cite
|
Sign up to set email alerts
|

A Rethinking of the Production Approach in IPCC: Its Objectiveness in China

Abstract: Abstract:The trade of harvested wood products (HWPs) and their feedstock increasingly affects the dynamics of the complete national HWP carbon pool ignored by the Production Approach (PA), the current universal method, proposed by the Intergovernmental Panel on Climate Change. Existing research also overlooks the inherent factors that lead to the non-objectiveness of PA that affects the potential carbon trade and the sustainable use of forestry resources. This study aimed to investigate such inherent factors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 37 publications
1
18
1
1
Order By: Relevance
“…Recent research results showed that the carbon stock was 470 TgC with an annual increment of 40 TgC in 2014 [21]. In the current research, the result of national carbon stock in the HWP pool is 570 TgC in 2011 and 706 TgC in 2014, which is higher than those of the existing researches.…”
Section: Discussioncontrasting
confidence: 61%
“…Recent research results showed that the carbon stock was 470 TgC with an annual increment of 40 TgC in 2014 [21]. In the current research, the result of national carbon stock in the HWP pool is 570 TgC in 2011 and 706 TgC in 2014, which is higher than those of the existing researches.…”
Section: Discussioncontrasting
confidence: 61%
“…Both studies employed the data from FAOSTAT but reached different results. The cumulative carbon stock by 2014 was estimated as 705.6 Teragrams Carbon (TgC) by Ji et al [14], which was significantly higher than the estimation by Yang et al’s [13] of only 473.3 TgC in 2015. Both studies ignored the stock change in retired wood products.…”
Section: Introductionmentioning
confidence: 85%
“…The carbon pool in HWP of China represents a continuous increasing carbon sink [12,13,14,15]. Yang et al [13] and Ji et al [14] estimated the carbon stock in China’s HWP by using the latest PA approach, as recommend by the IPCC. Both studies employed the data from FAOSTAT but reached different results.…”
Section: Introductionmentioning
confidence: 99%
“…Following the 17th session of the Conference of the Parties, carbon accounting of HWP is confined to products in use, where the wood was derived from domestic harvest [48]. The principle is the same as the production approache (PA), a universal approach during the second commitment period of the Kyoto Protocol [49]. The current study calculated the gate-to-gate CO 2 flux in which the system boundary disregarded trade and excluded carbon in imported wood-based panels [11].…”
Section: Ipcc Methodologymentioning
confidence: 99%